Historical dictionary of international relations - Lamb, Peter 1960-; Robertson-Snape, Fiona (Historical dictionaries of international organizations, 2017)
The Historical Dictionary of International Relations is a general guide to the theory and practice of the relations between states, and between states and other actors on the world stage. It introduces readers to the real world operations of international relations, and is thus concerned with the actual relations between states, organizations, groups and people. It also offers introductory information about the various theories, old and new, that help explain these relations, why they happen and the possible alternatives that might be available now or in the future. Moreover, some of the key thinkers of these theories are discussed. The Historical Dictionary of International Relations contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 200 cross-referenced entries on real world operations of international relations, the actual relations between states, organizations, groups and people.. This book is an excellent resource for students, researchers, and anyone wanting to know more about International Relations.